Reconstruction after Pelvic Bone Massive Resection: Evolution and Actuality of 3D-Printing Technology - Cosseddu, F; Shytaj, S; Ipponi, E; D'Arienzo, A; Capanna, R; Andreani, L (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
PURPOSE OF THE STUDY: Pelvic reconstructions after massive bone resections are among the most challenging practices in orthopedic surgery. Whether the bone gap results after a trauma, a tumor resection, or it is due to a prosthetic revision, it is mandatory to reconstruct pelvic bone continuity and rebuild the functional thread that connects spine and hip joint. Several different approaches have been described in literature through the decades to achieve those goals. MATERIAL AND METHODS: To this date, 3D-printed implants represent one of the most promising surgical technologies in orthopedic oncology and complex reconstructive surgery. We present our experience with 3D-printed custom-made pelvic prostheses to fulfi ll bone gaps resulting from massive bone loss due to tumor resections. We retrospectively evaluated 17 cases treated with pelvic bone reconstruction using 3D-printed prostheses. Cases were evaluated in terms of both oncological and functional outcomes. RESULTS: At the last follow-up, local complications were found in 6 cases (36%): in 4 (23.5%) of them the cause was a local recurrence of the disease, whereas only 2 (12.5%) had non-oncologic issues. The mean MSTS score in our population increased from 8.2 before surgery to 22.3 at the latest clinical control after surgery. DISCUSSION: 3D-printing technology, used to produce cutting jigs and prosthetic implants, can lead to good clinical and functional outcomes. These encouraging results are comparable with the ones obtained with other more frequently used reconstructive approaches and support custom-made implants as a promising reconstructive approach. CONCLUSIONS: Our data confi rm 3D-printing and custom-made implants as promising technologies that could shape the next future of orthopedic oncology and reconstructive surgery. KEY WORDS: custom made prosthesis, pelvic reconstruction, orthopedic oncology, cutting jigs, 3D-printing.
Keywords: Technology; nádory; 3D tisk; Printing, Three-Dimensional; retrospektivní studie; Humans; Pelvic Bones; technologie; pánevní kosti; lidé; Retrospective Studies; artrodéza; Neoplasms; Arthrodesis